1975
DOI: 10.1111/j.1532-5415.1975.tb00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychopharmacologic Investigations in Elderly Volunteers: Effect of Diazepam in Males†

Abstract: Forty male volunteers over the age of 60 took either a daily dose of diazepam (12 mg) or placebo for a two-week period. Differential responses to these compounds partially depended upon age and the initial symptom level. Diazepam produced sedative side effects, a modest antidepressant effect, and a reduction in memory. Placebo had an antianxiety effect in the relatively older subjects, and was associated with decreased fatique, improved memory and improved motor function. Considerable variability was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Chesrow et al (30), in the first published clinical study of Valium in geriatric patients, concluded that 95 percent of patients exhibiting behavioral disorders who received a daily dosage of 6 mg, showed moderate to marked reduction of symptoms; many who manifested depression and confusion also showed moderate to excellent improvement. However, in their more recent studies, Salzman et al (31) found that older subjects reported more consistent reductions in anxiety from placebo. Not only was the placebo useful as an antianxiety agent for the geriatric population, but it also reduced fatigue and improved memory and motor function.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Chesrow et al (30), in the first published clinical study of Valium in geriatric patients, concluded that 95 percent of patients exhibiting behavioral disorders who received a daily dosage of 6 mg, showed moderate to marked reduction of symptoms; many who manifested depression and confusion also showed moderate to excellent improvement. However, in their more recent studies, Salzman et al (31) found that older subjects reported more consistent reductions in anxiety from placebo. Not only was the placebo useful as an antianxiety agent for the geriatric population, but it also reduced fatigue and improved memory and motor function.…”
Section: Discussionmentioning
confidence: 93%
“…Failure to recognise the age-related changes that affect absorption, plasma binding, metabolism, excretion and end-organ response can lead to the development of toxic accumulation of drugs, increased susceptibility to drug interactions and potentially dangerous side effects. In prescribing for the elderly, it is wise to 31 4 1 remember Napoleon's words, "I do not want two diseases -one nature made, one doctor made" (11).…”
mentioning
confidence: 99%
“…The recall of information learned prior to medication may be facilitated by diazepam (Hinrichs et al 1984). On the other hand, many patients take BZ medications several times daily, and the memory-impairing effect of BZs may have greater impact for certain kinds of patients, such as cardiac patients (Frazure-Smith and Rolicz-Woloszyk 1982) or the elderly (Salzman et al 1975). The implications of laboratory tests of recall ability with BZs for the overall clinical status of patients' memory function should be evaluated with further clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing neuroleptics and benzodiazepines suggest that neuroleptics are more likely to be effective. Sedation, confusion, memory impairment, and ataxia are commonly reported side effects in older patients taking benzodiazepines, 70–78 and these side effects are likely to be more common in the older demented patient. Although not reported specifically in the elderly, paradoxical rage reactions and disinhibition have been reported with diazepam and chlordiazepoxide 79 .…”
Section: Benzodiazepinesmentioning
confidence: 99%